Genetic susceptibility to thyroid cancer: contributions of RET polymorphisms - Santos, Marina Silva dos (2013)
Thyroid cancer is the most common malignancy of the endocrine system, represents more than 1% of all malignancies and has an estimated annual incidence of 212,000 cases worldwide. The term differentiated thyroid carcinoma (DTC) comprises the subtypes papillary thyroid carcinoma (PTC) and follicular thyroid carcinomas (FTC), these subtypes represent the two most common subtypes of thyroid cancer (approximately 80% and 10% respectively). Despite its incidence DTCs have a good prognosis with relatively few metastases and deaths associated. The polymorphisms (variants in DNA sequence among individuals that have a frequency of at least 1% in a population) of RET proto-oncogene have been studied in different populations for association with susceptibility to thyroid cancer, but with inconsistent findings mainly in DTC. To clarify the contribution of single locus or haplotypes (polymorphisms that are transmitted through generations as a unit) of RET polymorphisms to genetic susceptibility to DTC among Portuguese patients, we conducted a case–control study by analyzing four well-characterized RET polymorphisms (G691S, L769L, S836S and S904S). To achieve this aim, the RET polymorphisms were genotyped and haplotype frequencies were estimated in a population of 282 individuals with DTC and in a control population of 254 individuals. Allele, genotype and haplotype distributions were compared among cases and controls. Patient population was subdivided according to several clinical parameters and allele, genotype and haplotype distributions were compared among the subgroups. The single locus analysis showed an overrepresentation of the S836S polymorphism in patients when compared to controls. Also the heterozygous genotypes of the G691S/S904S polymorphisms were overrepresented in cases diagnosed after the age of 45 years and the heterozygous genotype of G691S polymorphism revealed an overrepresentation in patients with tumors larger then 10mm of diameter at diagnosis. The haplotype analysis showed an overrepresentation of GGTC haplotype in patients particularly in those diagnosed after the age of 45 years. In conclusion, our data suggest that the S836S polymorphism may be associated with increased risk of DTC. Also the heterozygous genotype of the G691S/S904S polymorphisms seems to be associated with age of onset of DTC and additionally the heterozygous genotype of G691S polymorphism appeared to be in association with tumor size. Finally, one haplotype appears to be associated with increased risk of DTC particularly in those developed in later age (after the age of 45 years). These findings need to be confirmed by larger studies in order re-evaluate the role of these variants in the susceptibility to DTC.